Coping With On-Call Work: Current Knowledge to Support Women in the Emergency Services. Issue Volume 34:Issue s1(2019) (May 2019) - Jay, Sarah M; Vincent, Grace E; Roberts, Bernadette; Aisbett, Brad; Reynolds, Amy C; Paterson, Jessica L; Ferguson, Sally A
Abstract : Introduction: All Fire and Emergency Services (FES) personnel must balance FES work with their other responsibilities. Given that women tend to take on a greater responsibility for management of household/domestic activities than men, the on-call component of their FES work may be associated with very different challenges. Despite this, women have rarely been the focus of on-call research. Aim: To explore women's on-call experiences in the FES by examining coping styles and strategies, with the goal of helping to innovate the way women are supported in FES roles. Methods: Relevant findings from two studies are included. The first study involved FES personnel from two agencies in Australia (n=24) who participated in a semi-structured interview. The second study was an anonymous online survey to determine work characteristics, sleep, stress, and coping in on-call workers more broadly, with workers from all industries across Australia (n=228) invited to participate. Results: Interview data identified two major themes in terms of coping with on-call work. Support (from family, social, and work), planning, and preparation were identified as important in helping women cope in the context of on-call unpredictability. Results from the survey (43% women) showed that on-call workers were an engaged group in terms of their coping, with 67% classified as having a positive coping style and 58% of women indicating that they agreed/strongly agreed with the statement, "I cope well with on-call work." Discussion: Taken together, these data highlight engagement with positive coping by women who do on-call work, including in the FES. Importantly, positive coping strategies, such as talking about emotions, problem-solving, and seeking support have been linked to increased shift work tolerance in other populations. Coping style and strategies represent modifiable variables which could be specifically applied to assist women to manage the unique challenges associated with on-call work in the FES.